METHODOLOGICAL ASPECTS OF POSTGRADUATE EDUCATION IN PREVENTIVE MEDICINE - Свистельник, Андрей Владимирович; Ханин, Аркадий Лейбович; Альшевская, Алина Анатольевна (Medicine in Kuzbass, 2022)
Preservation of health (or prevention of diseases) is one of the main trends of modern medicine development. Focus on public health, protection from environmental threats, and establishing conditions for a healthy lifestyle are becoming priorities in healthcare. Complementing and developing prevention methodology, adapting to new requirements, and multidisciplinary training of healthcare professionals are top priorities. Currently, the knowledge base of preventive medicine is being updated, and training programs are being developed to train competent specialists.